What Do We Know about Performance-Based Financing? - Baasandorj, Lkhagvasuren; Lkhagvaa, Battur; Tsagaankhuu, Sarnai (Central Asian Journal of Medical Sciences, 2023)
As in other countries, health financing reform in Mongolia is based on the concept of universal coverage [1]. The Mongolia the Ministry of Finance of Mongolia with the technical assistance of the Asian Development Bank launched the “Health Sector Financing Improvement Project” in 2019-2022. This allows the need to achieve universal health coverage and to provide quality care and services that meet the health demands and needs of the people in an equally accessible way, without incurring financial risks [2,3]. Mongolia’s health care sector financing model has changed from an input-based financing model to an output-oriented model, and implemented the performance-based financing of health care and services as a reform [2]. Universal health coverage (UHC) is a growing policy priority in many countries, as well as a significant and increasing focus of attention at the international level, forming one of the targets of sustainable development goal 3 [4]. Performance‐based financing (PBF) or paying for performance (P4P) has received increased attention as a strategy for improving the performance of healthcare providers, organizations and governments since the early 2010s [5,6]. In PBF people are given money or other rewards if they carry out a particular task or meet a particular target [7]. This is a strategic purchasing mechanism which [8] becomes a common strategy to improve health sector quality [9].